2005
DOI: 10.1007/s00438-004-1094-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Aspergillus niger prolyl aminopeptidase

Abstract: We have cloned a gene (papA) that encodes a prolyl aminopeptidase from Aspergillus niger. Homologous genes are present in the genomes of the Eurotiales A. nidulans, A. fumigatus and Talaromyces emersonii, but the gene is not present in the genome of the yeast Saccharomyces cerevisiae. Cell extracts of strains overexpressing the gene under the control of its own promoter showed a fourfold to sixfold increase in prolyl aminopeptidase activity, but no change in phenylalanine or leucine aminopeptidase activity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
0
23
0
2
Order By: Relevance
“…PAP have been identified and characterised, e.g. in the ascomycetes A. oryzae and A. niger ( Matsushita-Morita et al 2010, Basten et al 2005. Both PAP have similar properties with a native molecular weight of~315 kDa and seem to be composed of six monomeric units.…”
Section: Fungimentioning
confidence: 98%
“…PAP have been identified and characterised, e.g. in the ascomycetes A. oryzae and A. niger ( Matsushita-Morita et al 2010, Basten et al 2005. Both PAP have similar properties with a native molecular weight of~315 kDa and seem to be composed of six monomeric units.…”
Section: Fungimentioning
confidence: 98%
“…In contrast, earlier studies of intracellular aminopeptidases from Aspergillus have indicated that expression is constitutive (Basten et al, 2001(Basten et al, , 2003(Basten et al, , 2005). This study definitively shows induction of TePAP when the peptide hydrolysate from casein (a protein rich in proline) is present in growth medium supplemented with a favoured carbon source (glucose).…”
Section: Discussionmentioning
confidence: 85%
“…A number of PAP-type activities in fungi have been reported (Bolumar et al, 2003;Fuke & Matsuoka, 1993;Hiwatashi et al, 2004), but no corresponding protein sequences have been assigned for these enzymes. However, more recently, one study by Basten et al (2005) identified a gene encoding PapA from Aspergillus niger and characterized the recombinant protein.…”
Section: Introductionmentioning
confidence: 99%
“…The other group consists of a multimeric protein that is either a tetramer or a hexamer obtained from Aeromonas sobria (Kitazono et al. 1994a), A. niger (Basten et al. 2005) and Streptomyces aureofaciens (Uraji et al.…”
Section: Introductionmentioning
confidence: 99%